Evaluation of the blood product characteristics of meat meal and hemoglobin with non-invasive methods in the VISNIR wavelength - Bökfi, Katalin; Nagy, Attila; Riczu, Péter; Gyug, Nikoletta; Petis, Mihály; Blaskó, Lajos; Tamás, János (Acta Agraria Debreceniensis, 2016)
The separate collection of poultry slaughterhouse trimmings and blood is partially solved in Hungary. Only properly prepared animal by-products, protein meals can be utilized as animal feed additive. However, different protein meals are appropriate for feeding different animal species. That is the reason why it is important to avoid accidental cross contamination of the products. Meat and blood meal produced on the same technological line, therefore mixing of the products can happen in various proportions during the shift of production. Thus the aim of this study is to develop a spectral method which will allow to estimate the ratio of meat and blood protein meal in the final product. During the test the products were mixed in different proportions and were examined by the spectral method. Measurements were conducted with AvaSpec 2048 spectrometer in visible (VIS) and in near infrared (NIR) wavelength range (400–1000 nm) to define the spectral differentiation of the different meal products. Significant difference can be detected in spectral reflectance between the meat and blood product in the VIS-NIR range. The blood product has a characteristic spectral property: in the range of 600 and 735 nm reflectance values are increasing following a sigmoid curve. This property is not observed in the case of meat meal: close to linear rising is detected. Effective protein rate and purity detection could be made by Blood Product Sensitive Mixing Index (BPSMI – R930/R600), and by the calculation of inflection point in 600–735 nm.